(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
Objective — to evaluate the predictive value of the first‑trimester leptin/adiponectin (L/A) ratio for early detection of pre‑eclampsia in obese pregnant women. A prospective cohort of 190 women (130 with BMI ≥ 30 kg/m², 60 controls) was examined at 11–13 weeks. An L/A threshold ≥ 5 predicted pre‑eclampsia with 88 % sensitivity and 81 % specificity. Health‑economic modelling indicated a 14‑fold return on investment through aspirin prophylaxis.